From Emancipation to Women’s Education: An Intellectual History of R.A. Kartini’s thought 1899–1904 - Resti Nur Isnaeni; Mukhamad Shokheh (Universitas Islam Negeri Sumatera Utara, 2026)
This study examines the evolution of Raden Ajeng Kartini’s thinking from the concept of emancipation to the establishment of a school for girls during the period 1899–1904. The research is motivated by the conditions of Javanese society during the colonial era, which was still influenced by patriarchal culture and feudal customs that restricted women’s freedom and access to education. The study aims to explain the emergence of Kartini’s critical consciousness, the development of her ideas on emancipation, and the realization of her ideas through education. The research employs Kuntowijoyo’s historical method, which encompasses heuristics, verification, interpretation, and historiography, utilizing colonial archives, Kartini’s letters, contemporary newspapers, and various supporting literature. The results of the study indicate that the experience of being confined fostered the growth of Kartini’s critical awareness of gender injustice, which evolved into ideas of emancipation emphasizing freedom, equal rights, and education as a means to elevate women’s dignity. These ideas were realized through the establishment of a girls’ school in Rembang as a concrete manifestation of her struggle. This study demonstrates that the transformation of Kartini’s thinking from criticism of gender inequality to educational practice contributes to the fields of intellectual history, women’s historiography, and the history of education in Indonesia.